The Oracle Bone Inscriptions from Huayuanzhuang East - Schwartz, Adam C. (Library of Sinology, 2020)
The Huayuanzhuang East oracle bone inscriptions form a corpus of more than 2500 individual divination accounts, which were engraved on turtle shells and bovine scapulae in the late Shang dynasty (c. 1200 B.C.). The book offers the first complete English annotation of these fascinating epigraphic texts and introduces the reader to key aspects of daily life in early Chinese civilization.